Inheritance Distribution under Dayak Ngaju Customary Law in the Kedamangan of Jekan Raya, Palangka Raya City (A Case Study of the Decision of the Kedamangan of Jekan Raya District, Palangka Raya City Number 056/DKA-KJR/V/2022) - Marselino, Fernando; Wijaya, Andika; Nugraha, Satriya (Dinasti Research, 2025)
This article examines the implementation of inheritance distribution based on the Dayak Ngaju customary law through a case study of Decision Number 056/DKA-KJR/V/2022 by the Customary Court of Kedamangan Jekan Raya, Palangka Raya City. The study adopts a juridical-empirical approach by combining normative legal analysis with field observations on how inheritance disputes are resolved within the community. The findings reveal that inheritance settlement among the Dayak Ngaju people is carried out through a customary court forum known as the Kerapatan Mantir Adat, led by Damang and Mantir (customary judges). The dispute in this case arose when the father (Respondent) sold inherited land without sharing the proceeds with his children (Petitioners) as rightful heirs. The resolution process involved stages from pre-conflict negotiation to formal adjudication, emphasizing the principles of deliberation, consensus, harmony, and justice in accordance with Dayak Ngaju customary values. The final decision of the customary court affirmed gender equality in inheritance rights and mandated a fair and equal distribution of the estate. This study underscores the vital role of customary institutions not only in conflict resolution but also in preserving social harmony and sustaining local wisdom within Indonesia’s pluralistic legal system.